Ayurvedic Approach for Shwitra- A Case Study - Shalini; Chakraborty Subhrajyoti (International Journal of Ayurveda and Pharma Research, 2021)
Skin is one of the most important and visible organ of our body. Skin anomalies create physical as well as psychological problems in an individual. Among different variety of Kustha, Shwitra is considered as one of them in the Ayurvedic classics which occur due to vitiation of Tridoshas and Dhatus like Rakta, Mamsa and Meda. Shwitra can be correlated with vitiligo or leucoderma, where it manifest as white patch on the skin due to partial or complete loss of skin pigmentation and causes cosmetic imbalance of the body. Vitiligo is an autoimmune disease and it may be associated with other autoimmune diseases such as pernicious anaemia, addison disease and diabetes mellitus results in destruction of melanocytes thus causing depigmentation. A female patient, aged 36 years suffering from white patches in left forehead region for last 2 years and she was treated with both Sodhan and Shaman Chikitsa for a period of 3 months. Result was assessed from the changes in the size of patch and photographs. Proper written consent was taken from the patient prior to the study. Follow up was done at 1 month interval and after 3 months there was marked improvement seen in patch and colour. The present study indicates different prospective of treatment for Shwitra kustha and it provides cost effective as well as safe treatment of the disease. This study shows a new dimension in the treatment for Shwitra and could be carried out for statistical significant study.